Adolescent Perspectives on Fathering and Psychological Development in Minangkabau’s Matrilineal Society - Herdianti, Adissah Putri; Hartati, Niken; Mardianto, Mardianto (Universitas Muhammadiyah Surakarta, 2025)
In Minangkabau’s matrilineal society, fathers are often perceived as less central, yet adolescents’ interpretations of paternal involvement may illuminate differences in their psychological development. This study aimed to describe how adolescents construe fathers’ involvement across domains and how it is perceived to shape psychological development. Seventy Minangkabau adolescents (31 male, 39 female; aged 12–20) were recruited via purposive sampling; all co-resided with their biological father and mother in West Sumatra. Data were collected using a researcher-developed open-ended questionnaire, analyzed through a six-phase thematic analysis, and verified via participant confirmation. Findings revealed three overarching domains: (1) fathers’ involvement in day-to-day caregiving (positive patterns;academic and religious guidance, practical support, discipline and character values, quality time and humor; negative/minimal patterns; fathers substituting for mothers), (2) paternal responses when adolescents experience stress (listening and open communication, offering advice and solutions, motivating presence, or emotional absence), and (3) fathers’ roles in decision-making (advisor and companion, support and trust, boundary setting, facilitation of freedom and autonomy, role modeling, and minimal influence). Overall, a blend of warmth, structure, and meaningful adolescent voice from fathers was perceived to strengthen self-regulation, self-confidence, school connectedness, and social competence; conversely, limited presence, permissive or authoritarian patterns, and emotional absence were linked to more fragile adjustment. These results imply that culturally grounded fathering practices combining guidance, clear limits, and adolescent participation are promising levers for family interventions in the Minangkabau context.